Simulation of the Wide-Band DAD Converters - Marcinkevicius, A. (Elektronika ir Elektrotechnika, 1998)
Methodics for the calculation of the trasient processes in the wide band integrated AD converters using multi-deflection method has been created. Algorithm for the signals simulation in the input of the comparators has been des-cribed. Results of the short impulse (ns range) simulation in the signal transmition lines with various length are chown. Created mathematical model allows to simulate transient processes and to analyze dynamic characteristics in the topological circuits of the integrated AD converters in the ns range.